Success Factor Management Analysis of Self-Management System For Building Projects - Jamal; Albani Musyafa; Faisol AM; Fitri Nugraheni (University of Technology Yogyakarta, 2022)
The requirement of project management in construction is needed to be able to set priority aspects of implementation from the beginning to the end, to make it succeed and happen as a plan. Self-management is one of the managements to the owner and some scope is to universities that have resources qualified as self-management. Success factor analysis of self-management aims to determine the priority success factors and characteristics of buildings that can be used for self-management. The analytical method used in this research is Analytical Hierarchy Project or AHP. Based on the results of the study, it was obtained 4 respondents who met the criteria for self-management and 10 factors of success, namely quality with 21.33%, leadership / managerial 16.94%, cost 16.89%, 15.68% customer satisfaction, administration 8%, human resources 7.40%, and the other factors such as time with 4.79%, suppliers 3.24%, labor 3.17%, and place characteristics 1.99%. The characteristics of buildings can be done independently, namely; having location or place of development that is owned by the community in a certain area, possessing the development that empowers human resources belonging to mass organizations and community groups, and owning a team of consultants and supervisors to improve planning, scheduling, and increased supervision.